PHOSPHORUS OXYNITRIDE PON, A SILICA ANALOGUE: STRUCTURE AND COMPRESSION OF THE CRISTOBALITE-LIKE PHASE; P -T PHASE DIAGRAM - Leger J.M.; Haines J.; Chateau C.; Bocquillon G.; Schmidt M.W.; Hull S.; Gorelli F.; Lesauze A.; Marchand R. (My University, 2001)
The structure of the cristobalite-like polymorph of phosphorus oxynitride PON has been refined using neutron powder diffraction data. It is tetragonal, space group I&4macr;2d, Z=4. The four P-(O,N) distances are equal but the tetrahedron is compressed along c. In AX2 ABX4 compounds, the tetragonal I&4macr;2d or I&4macr; structure is obtained when the average ratio of the cation to anion radius is below 1.186, whereas the tetragonal P41212 or orthorhombic C2221 structure is obtained at low temperatures for larger ratios. The cell parameters of this PON polymorph have been determined as a function of hydrostatic pressure by in situ angle dispersive X-ray powder diffraction in a diamond-anvil cell. Under truly hydrostatic pressure, a strong anisotropic behavior is observed with the c parameter being nearly incompressible. Very slight anisotropic stress strongly modifies the high-pressure behavior. According to the pressure-temperature conditions of treatment, three phases, cristobalite-, moganite-, and quartz-like, have been obtained by quenching experiments, and the P-T phase diagram of PON was derived. The high-pressure behavior of the α-quartz, moganite, and cristobalite-like polymorphs of PON and SiO2 discussed.
Keywords: CRISTOBALITE; STRUCTURE; HIGH-PRESSURE; PHASE DIAGRAM; X-RAY DIFFRACTION